Hydrographic Analysis of Oyo Hilir River Flood using SCS-CN Method with HEC-HMS and HEC-RAS 6.6 Integrated Modeling - Endah Theresya; Anggi Hermawan; Andrea Sumarah Asih (Universitas Islam Raden Rahmat, Malang, 2026)
The Oyo Hilir River in Bantul Regency is an area with a high level of flood vulnerability due to rainfall intensity, changes in land use, and river morphological characteristics. Repeated flooding events have an impact on community activities in downstream areas. This study aims to analyze the flood discharge of the Oyo Hilir River design and map the distribution and area of the flood-affected area based on the classification of inundation depth. The research was conducted on the Oyo Watershed (DAS) with a focus on the downstream segment of the river along ±14 km, starting from the confluence of the Oyo–Urang River to the Oyo–Opak River. The data used included rainfall for the period 2004–2023, Digital Elevation Model (DEM), and data on the characteristics of supporting watersheds. Hydrological analysis was carried out through rainfall frequency analysis using AProb and flood hydrographic modeling using the Soil Conservation Service–Curve Number (SCS-CN) method on HEC-HMS, which was then used as an input for two-dimensional hydraulic modeling using HEC-RAS version 6.6. The results showed that the peak discharge of the flood at the 2-year return period was 307.6 m³/second with a peak time at the 16th hour. The largest affected area is in Selopamioro Village, Imogiri District, with an inundation area of 323.62 ha dominated by high flood depth (>3 m). The results of this study are expected to be the basis for flood mitigation planning and sustainable management of the Oyo Hilir River.